Znaczenie pracy z książką drukowaną dla podopiecznych świetlicy szkolnej - Prokosz, Małgorzata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article tackles the issue of research describing the decline in number of readers amongst children in Poland. The author points to the main reasons for such phenomenon, subsequently analyzing cognitive, moral and therapeutic benefits of the contact with printed books. The summary stresses some examples of good practices concerning encouraging children, also those with special educational needs, to read, i.e. feasible methods that are possible to accomplish by the tutors in the day-care school centers.
Keywords: book; reading books; school day-care centers; special-need child; therapy reading